Corrigendum to “Accumulation and potential for transport of microplastics in stormwater drains into marine environments, Perth region, Western Australia” [Mar. Pollut. Bull. 168 (2021) 112362] - Lutz, N.; Fogarty, J.; Rate, A.; Hackett, Mark (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
The authors regret that the original manuscript failed to appropriately acknowledge all sources of intellectual and technical contribution, which warrant co-authorship. Dr Mark J Hackett (School of Molecular and Life Sciences, Curtin University, Bentley 6102 WA, Australia) is now recognised as a co-author of this manuscript with respect to intellectual input into the design of ATR-FTIR experiments and interpretation of the ATR-FTIR spectra. Dr Hackett is also recognised as the sole co-author responsible for training the first author of this paper in the use of ATR-FTIR research equipment. The ATR-FTIR equipment used for this study is housed within the School of Molecular and Life Sciences at Curtin University, and all authors gratefully acknowledge Curtin University for providing access to this equipment. The authors would like to apologise for any inconvenience caused. Natasha Lutz: Conceptualization, Methodology, Software, Data curation, Investigation, Formal analysis, Visualization, Writing – original draft, Writing – review & editing. James Fogarty: Data curation, Formal analysis, Methodology, Writing – review & editing, Supervision. Andrew Rate: Conceptualization, Methodology, Writing – review & editing, Supervision. Mark J. Hackett: Investigation, Data curation, Visualization.